Telehealth in Acute Care: Pay Parity and Patient Access - Çakıcı, Özden Engin; Mills, Alex F. (Manufacturing and Service Operations Management, 2025)
Problem definition: In response to the increased use of telehealth to replace traditional office visits with a physician, several U.S. states have recently adopted telehealth pay-parity policies. Such policies state that payers must reimburse healthcare providers for telehealth services at the same rate that would apply if those services had been provided in a traditional office setting. But health policy researchers have pointed out that telehealth may not be as effective as a traditional office visit for acute care. Specifically, telehealth is associated with increased probability of a subsequent office visit (a “duplicate visit”). We examine whether telehealth pay-parity policies are effective at improving access to acute care, and under what conditions. Methodology/results: We use a three-stage game-theoretic model to study the impact of telehealth pay parity. In the first stage, the payer sets a reimbursement policy for telehealth visits. In the second stage, a healthcare provider commits a portion of its capacity to telehealth, and in the third stage, patients arrive and choose between telehealth and office visits according to an equilibrium queueing network. We find structural results for the equilibria and characterize the equilibria in closed-form. When the chance of a duplicate visit is moderate (neither too high nor too low), pay parity leads providers to allocate too much capacity to telehealth, resulting in lower overall patient access than could be otherwise achieved. We characterize a reimbursement level that avoids this misalignment and maximizes patient access, which we show is less than parity. Managerial implications: The literature shows that patients receiving acute care via telehealth may be more likely to require a duplicate, in-person visit to resolve their health concern. In the fee-for-service environment that is common in the United States for acute care, duplicate visits resulting from telehealth lead to an incentive alignment problem because they generate extra work and provider revenue, without any corresponding increase in patient access. Legislating pay parity for telehealth can lead to providers committing more capacity to telehealth, which may not always be good. However, there is good news in that all parties (payers, providers, and patients) would be better off if duplicate visits could be decreased. Policy makers should understand these implications before enacting policies that affect reimbursements for telehealth. Funding: Support for this project was provided by a PSC-CUNY Award, jointly funded by The Professional Staff Congress and The City University of New York. Supplemental Material: The online appendix is available at https://doi.org/10.1287/msom.2022.0345 .